Recent developments in the management of recurrent Clostridioides difficile infection. (April 2020) - Mendo-Lopez, Rafael; Villafuerte-Gálvez, Javier; White, Nicole; Mahoney, Monica V.; Kelly, Ciaran P.; Alonso, Carolyn D.
Abstract: Clostridioides (formerly Clostridium ) difficile is responsible for a substantial burden of nosocomial infection. Recurrent C. difficile infection (rCDI) remains a concern due to its high morbidity, mortality, and cost. Despite the updated 2017 IDSA C. difficile treatment guidelines, there remains a lack of well-studied preventive control measures and treatment modalities for rCDI. There are ongoing efforts to develop novel therapies, such as new antibiotics with a lesser impact on gut microbiota and more targeted therapies, such as bacteriotherapy. This mini review highlights key rCDI management updates, preventive measures and ongoing research on novel treatment strategies including bacteriotherapy. Highlights: Recurrent C. difficile infection (rCDI) remains a significant concern due to its high morbidity and mortality. We evaluate the current management proposed on the 2017 IDSA guideline and compare with the previous guidelines. We review the outcomes of the ongoing trials related to novel antibiotics and bacteriotherapy. Bezlotoxumab has proven effectiveness for the prevention of rCDI.